2021
DOI: 10.1021/acsami.0c17739
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Driving between 2D Heterostructures and Surface Functionalization for Surpassing Binary Logic Devices

Abstract: Recently, for overcoming the fundamental limits of conventional silicon technology, multivalued logic (MVL) circuits based on two-dimensional (2D) materials have received significant attention for reducing the power consumption and the complexity of integrated circuits. Compared with the conventional silicon complementary metal oxide semiconductor technology, new functional heterostructures comprising 2D materials can be readily implemented, owing to their unique inherent electrical properties. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The vdW heterostructure with a charge trap‐free interface can be implemented without lattice mismatch, owing to the dangling bond‐free surface nature. [ 29,30 ] The corresponding Raman peaks for each layer also indicate the existence of α ‐In 2 Se 3 , CIPS (Figure 1e), and h‐BN (Figure S1, Supporting Information) in the fabricated vdWHs.…”
Section: Resultsmentioning
confidence: 94%
“…The vdW heterostructure with a charge trap‐free interface can be implemented without lattice mismatch, owing to the dangling bond‐free surface nature. [ 29,30 ] The corresponding Raman peaks for each layer also indicate the existence of α ‐In 2 Se 3 , CIPS (Figure 1e), and h‐BN (Figure S1, Supporting Information) in the fabricated vdWHs.…”
Section: Resultsmentioning
confidence: 94%
“…[ 55 ] Four logic states were also generated in inverters composed of two heterojunction NDT devices with N‐shaped transfer I – V curves. [ 65 ] Finally, a four‐state function was realized by using an NDT device with a Λ‐shaped I – V curve. In this MVL gate, binary inputs applied to the drain and gate terminals in different combinations were converted into a four‐state output.…”
Section: Mvl Devices Based On Design Of Transfer Id–vg Characteristicsmentioning
confidence: 99%
“…[55] Four logic states were also generated in inverters composed of two heterojunction NDT devices with N-shaped transfer I-V curves. [65] Finally, a four-state function was realized by using an NDT device with a Λ-shaped I-V c) Reproduced with permission. [28] Copyright 2016, American Chemical Society.…”
Section: Ndt Devicesmentioning
confidence: 99%
“…Another strategy for establishing a ternary inverter and even a quaternary inverter can be demonstrated by introducing p-type, ambipolar and n-type TMD materials with appropriate threshold voltages. 140…”
Section: Logic Gate and Integrated Circuit Enabled By Tmd Fetsmentioning
confidence: 99%
“…Taking a step further, multivalued logic units are alternative candidates with great promise for superseding the integration density limitation of logic devices. 140 A theoretical study revealed that ternary and quaternary logic devices can replace binary logic devices with 36% and 50% fewer interconnecting lines, respectively. 141 In 2017, Huang et al constructed a tunable inverter composed of black phosphorus (BP) transistors in series with an n-MoS 2 FET with variable channel length, achieving a transition from a typical binary logic inverter to a tunable ternary inverter (Fig.…”
Section: Invertermentioning
confidence: 99%